Blood Pressure, Heart Rate Variability, and Adiposity in Caribbean Pre-pubertal Children - Grandemange, Morgane; Costet, Nathalie; Doyen, Matthieu; Monfort, Christine; Michineau, Léah; Saade, Marie-Béatrice; Multigner, Luc; Cordier, Sylvaine; Pladys, Patrick; Rouget, Florence (Frontiers in Pediatrics, 2019)
Childhood obesity prevalence has increased over the last 30 years. The Heart Rate Variability (HRV) studies performed in adults suggest a possible relation between abnormal autonomic regulation and hypertension in the situation of overweight or obesity. Objective: The aims of this study were to explore the early relationships between adiposity and blood pressure and HRV in pre-pubertal children. Methods: Data were collected during the medical examination of the follow-up at 7 years of the TIMOUN mother-child cohort in Guadeloupe (French West Indies). Body Mass Index z-score (zBMI), sum of tricipital and subscapular skinfold thickness, percentage of fat mass, and Waist-to-Height Ratio were measured. A global corpulence score was computed using a Principal Component Analysis. Systolic Blood Pressure (SBP) and HRV parameters (cardiac holter monitoring) were collected under 2 conditions (calm and tachycardial period). Relations between HRV, SBP, and the corpulence score were studied with restricted cubic splines models, and linear regression models. The age at adiposity rebound (AR) was estimated from the individual growth curves. Results: 575 children were included in the SBP study (mean age: 7.7 years, from 85 to 99 months). SBP was linearly correlated with the corpulence score and the zBMI. An increase of 1 in the zBMI was associated with an increase of 2.3 (±0.28) mmHg in SBP. The effect-size of zBMI on SBP was higher in children with early age at AR. Compared to children with normal BMI, children with a zBMI <-2SD had their RMSSD, SDNN, LF and HF indicators in tachycardial conditions significantly reduced by -30%, -21%, -37% and -48% respectively. In boys with a zBMI >2SD, we observed a global increase of all HRV parameters (tachycardial conditions), particularly the LF (β = 0.43 (±0.18)). Conclusion: In pre-pubertal period, a positive correlation between adiposity excess and SBP was observed with significant changes in HRV in boys, arguing for an already abnormal autonomic regulation and for early preventive intervention in the infancy period, particularly in case of overweight or obesity. Thinness was associated with a reduction of almost all the HRV parameters studied, when compared to normal corpulence, suggesting a decrease in autonomic influence.